Redirecting Nonurgent Patients From the Pediatric Emergency Department to Their Pediatrician Office for a Same-Day Visit—A Quality Improvement Initiative. Issue 12 (1st December 2022) - Wolski, Thomas P.; Jamerino-Thrush, Jennifer; Bigham, Michael T.; Kline-Krammes, Sarah; Patel, Nirali; Lee, Timothy J.; Pollauf, Laura A.; Joyce, Crystal N.; Kunka, Sarah; McNinch, Neil L.; Jacobs, Michelle; White, P. Cooper
Abstract : Objectives: Providing high-quality care in the appropriate setting to optimize value is a worthy goal of an efficient health system. Consequences of managing nonurgent complaints in the emergency department (ED) have been described including inefficiency, loss of the primary care–patient relationship, and delayed care for other ED patients. The purpose of this initiative was to redirect nonurgent patients arriving in the ED to their primary care office for a same-day visit, and the SMART AIM was to increase redirected patients from 0% of those eligible to 30% in a 12-month period. Methods: The setting was a pediatric ED (PED) and primary care office of a tertiary care pediatric medical system. The initiative utilized the electronic health record to identify and mediate the redirection of patients to the patient's primary care office after ED triage. The primary measurement was the percentage of eligible patients redirected. Additional measures included health benefits during the primary care visit (vaccines, well-visits) and a balancing measure of patients returned to the PED. Results: The SMART AIM of >30% redirection was achieved and sustained with a final redirection rate of 46%. In total, 216 of 518 eligible patients were redirected, with zero untoward outcomes. The encounter time for redirected patients was similar for those who remained in the PED, and additional health benefits were appreciated for redirected patients. Conclusions: This initiative redirected nonurgent patients efficiently from a PED setting to their primary care office. The process is beneficial to patients and families and supports the patient-centered medical home. The balancing measure of no harm done to patients who accepted redirect reinforced the reliability of PED triage. The benefits achieved through the project highlight the value of the primary care–patient relationship and the continued need to improve access for patients and families.